Analysis of Criminal Law Reform Regarding the Principle of Material Legality in Law Number 1 of 2023 concerning the National Criminal Code (Lex Journal : Kajian Hukum dan Keadilan, 2025)
Currently, Indonesia is implementing a renewal of the Dutch colonial Criminal Code (KUHP) into the National Criminal Code. One of the significant changes between the colonial Criminal Code and the National Criminal Code is the expansion of the principle of legality. In the Colonial Criminal Code, only the principle of formal legality is recognized, namely, the benchmark for criminalizing someone is the law (written law), while in the National Criminal Code, it adopts the principle of formal legality and also the principle of material legality (unwritten law/customary law). This study aims to analyze whether the implementation of the principle of material legality is in accordance with the principles of justice and humanity. The results of the study indicate that the expansion of the principle of material legality, namely the point that the National Criminal Code wants to emphasize, is the harmony and compatibility between written law (civil law) and unwritten law (living law). If there is a conflict between written and unwritten law, the judge is obliged to prioritize the unwritten law. This study concludes that the principle of material legality provides the idea of a balance between justice and legal certainty, providing an opportunity for law enforcement officers to enforce the law in accordance with the conscience and justice of society.